Hong Kong Poison Information Centre: Annual Report 2014. Issue 6 (November 2015) - Chan, YC; Tse, ML; Lau, FL
Objective: To report and analyse the poisoning data of Hong Kong Poison Information Centre (HKPIC) in 2014. Methods: In 2014, all poisoning cases received by HKPIC were retrieved from its database [Poison Information and Clinical Management System (PICMS)] for analysis. Results: A total of 3, 609 poisoned cases were analyzed. There were 1, 587 male patients (44.0%), 2, 000 female patients (55.4%) and 22 sex unspecified patients (0.6%). Middle aged group (30-39 years) was the commonest and composed of about one-fifth (20.3%) of the poisoning cases while about two-third (66.2%) of them were between 20 and 59 years old. Common causes for poisoning were suspected self-harm/suicidal attempt (42.2%), unintentional exposure (16.5%) and abusive substances use (12.9%). Excluding the common co-ingestant ethanol, five commonest types of poison exposed were benzodiazepine, paracetamol, zopiclone, Chinese herbal medicine and household products. Majority of the patients were managed with supportive measures, and 14.7% and 15.0% of them were treated by decontamination and antidotes respectively. Most cases had uneventful recovery; 0.9% of the poisoning resulted in death and 5.0% had major outcomes. Conclusions: This 9th annual report provided updated epidemiological information on poisoning pattern in Hong Kong and highlighted important changes in comparing with our previous reports. (Hong Kong j.emerg.med. 2015; 22:376-387)